Online travel review posting intentions: a social exchange theory perspective. Issue 4 (2nd October 2021) - Bakshi, Shuchita; Gupta, Deepak Raj; Gupta, Anil
ABSTRACT: The present study investigates various costs and benefits associated with individuals' intentions to post online travel reviews and to understand this, the study applies social exchange theory as the base model. The results revealed that altruism, reputation, economic rewards and venting negative feelings positively influence review posting intentions while cognitive and executional costs negatively influence review posting intentions. Further, Innovativeness moderates the relationship between altruism and behavioural intentions and venting negative feelings and behavioural intentions. The findings indicate that cognitive and executional costs reduce the intentions of travelers to post reviews online. Therefore, service providers must focus on user-friendly technology to reduce these costs.